The gondoliers operetta - Sullivan, Arthur 1842-1900; Gilbert, William S. 1836-1911 (Opus Arte, 2006)
The impoverished Duke and Duchess of Plaza-Toro come to Venice in search of the heir to the throne of Barataria, inconveniently mislaid at birth and betrothed to their daughter. The most likely candidates are two handsome gondoliers, far more interested in parties than politics and, what's more, just married! It takes the help of the nursemaid to unravel the knots in this particularly twisty tale